When will we talk about Hitler? : German students and the Nazi past - Oeser, Alexandra (Worlds of memory, 2019)
Education in the service of democracy -- Talking about the Nazi past in class and succeeding at school -- Gender, family and the Nazi past(s) -- The Nazi past as an everyday resource for adolescents -- The social and cultural limits to appropriations of the Nazi past -- Peer-group dynamics and playful uses of the past -- Conclusion: From memory to appropriation(s).